Implementasi Focusky Dan Kahoot Membantu Meningkatkan Motivasi Belajar Peserta Didik Terhadap Matematika - Nuraeni, Irna; Ni'mah, Khomsatun; Rahayu, Diar Veni (Pendidikan Matematika Universitas PGRI Yogyakarta, 2020)
This study aims to determine the implementation of Focusky and Kahoot in increasing motivation to learn SMK students. This research uses descriptive research methods supported by qualitative and quantitative data. The main purpose of descriptive research is to get a detailed picture of a situation while answering questions such as who, when where, and how. The type of descriptive research was chosen because this study aims to describe matters related to the implementation of the Focusky and Kahoot applications in increasing students' motivation towards mathematics in vocational high schools. The subjects in this study were 5 students of class X SMK Al Huda Sariwangi. Data collection techniques used in this study were questionnaires and tests. From the results of the study, it can be revealed that learning by implementing the Focusky and Kahoot applications, in the learning process creates a more interesting, fun, and interactive learning atmosphere so that it has a positive impact on increasing student learning motivation and makes it easier for students to understand the material delivered by the teacher.Keywords: Focusky, Kahoot, Learning Motivation